2006
DOI: 10.1038/ni1325
|View full text |Cite
|
Sign up to set email alerts
|

NKG2D-mediated signaling requires a DAP10-bound Grb2-Vav1 intermediate and phosphatidylinositol-3-kinase in human natural killer cells

Abstract: NKG2D is an important immunosurveillance receptor that responds to stress-induced ligand expression on tumors and virus-infected cells. Human natural killer cells express NKG2D and require the transmembrane adaptor DAP10 to initiate their full cytotoxic activation. However, DAP10 has no immunoreceptor tyrosine-based activation motif and thus the mechanism of recruiting 'downstream' effector proteins is unclear. We show here that binding of the p85 subunit of phosphatidylinositol-3- kinase to DAP10 could not by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
242
1
1

Year Published

2007
2007
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 245 publications
(248 citation statements)
references
References 49 publications
4
242
1
1
Order By: Relevance
“…To our knowledge, this is the first report demonstrating that the activation of PKA type I mediated by Like TCR, NCR and CD16 are associated with adapter proteins (such as CD3, DAP12 and FcRI-) which bear Immunoreceptor Tyrosine-based Activating Motifs (ITAM) and recruit the tyrosine kinases ZAP70 and Syk [35]. In contrast, NKG2D is associated with the adapter protein DAP10 which contains an YINM motif and recruits the adapter Grb2 and the kinase PI3K [36,37]. All these adapter proteins need to be phosphorylated by kinases of the Src family (such 18 as Lck) to transmit their activating signal [35].…”
Section: Discussionmentioning
confidence: 93%
“…To our knowledge, this is the first report demonstrating that the activation of PKA type I mediated by Like TCR, NCR and CD16 are associated with adapter proteins (such as CD3, DAP12 and FcRI-) which bear Immunoreceptor Tyrosine-based Activating Motifs (ITAM) and recruit the tyrosine kinases ZAP70 and Syk [35]. In contrast, NKG2D is associated with the adapter protein DAP10 which contains an YINM motif and recruits the adapter Grb2 and the kinase PI3K [36,37]. All these adapter proteins need to be phosphorylated by kinases of the Src family (such 18 as Lck) to transmit their activating signal [35].…”
Section: Discussionmentioning
confidence: 93%
“…Further, in this model, coupling of Grb2 complexes to DAP10 was necessary and sufficient for the recruitment and activation of Vav1, SLP76 and PLCg2. 70 This observation explains how NKG2D, without using adaptors such as LAT can effectively recruit PLCg2 leading to cytotoxicity. However, this study does not explain how the upstream events initiated from NKG2D/DAP10/p85 regulate cytokine generation.…”
Section: Discussionmentioning
confidence: 96%
“…Recent studies in NK and other cell types have indicated potential cross talks between PI3K and PLCg2 pathways. 70,71 Leibson laboratory has shown that binding of PI3K-p85 along with Grb2-Vav1 complexes was necessary for full calcium release and cytotoxicity. 70 NKG2D/DAP10 complexes can recruit combinations of p85a and Grb2 molecules, both of which bind to DAP10 by the YINM motif.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Besides expression of several receptors that mediate natural cytotoxicity, NK cells also express CD16 which mediates antibody-dependent cellular cytotoxicity (ADCC) against IgG-coated target cells [10][11][12][13]. While NK cell activating receptors like NKp30, NKp44, NKp46, and CD16 associate with the transmembrane adaptors CD3δ, FcRγ, or DAP12 that contain a cytoplasmic immunoreceptor tyrosine-based activation motif (ITAM) [14], NKG2D associates with the adaptor protein DAP10 which contains a cytoplasmic YINM motif [15][16][17][18][19]. The ligation or antibody dependent cross linking of the ITAM-dependent receptors initiates NK cell signal transduction cascade by phosphorylation of tyrosine residues located within conserved ITAM sequences through Src protein tyrosine kinase (PTK) family [20].…”
Section: Introductionmentioning
confidence: 99%